Improving the Ability to Write Description Text Using Audio-Visual Media in Grade VIII Students of SMP Negeri 20 Ambon - Wailisahalong, Fitriyani; Sasabone, Carolina; Somelok, Grace (Universitas Pattimura, 2024)
This study seeks to enhance the descriptive writing abilities of class VIII-1 students at SMP Negeri 20 Ambon through the utilization of audio-visual media. This study employs the classroom action research (CAR) methodology. The data analysis revealed discrepancies among Cycle I, Cycle II, and Cycle III for the pupils of class VIII-1 at SMP Negeri 20 Ambon. In Cycle I, 21 students failed to reach the Minimum Mastery Criteria (KKM), resulting in a failure percentage of 95.45% (21/22 × 100%), whereas one student achieved the KKM, yielding a success rate of 4.45% (1/22 × 100%). The mean score achieved in instructing descriptive text writing through audio-visual media for eighth-grade students in class VIII-1 at SMP Negeri 20 Ambon is 44.03. In Cycle II, the outcomes of the descriptive text writing assessment utilizing audio-visual media for VIII-1 grade students at SMP Negeri 20 Ambon indicated that 20 students failed to achieve the Minimum Mastery Criteria (KKM) of 75, resulting in a failure rate of 20/22 × 100% = 90.90%. Simultaneously, two students achieved the Minimum Mastery Criteria (KKM) established by the institution, which is 75, resulting in a success rate of 2/22 × 100% = 9.09%. In Cycle III, three students failed to fulfill the Minimum Mastery Criteria (KKM), resulting in a failure rate of 3/22 × 100% = 13.65%.